Biosafety laboratory risk assessment - Na Li; Lingfei Hu; Aijun Jin; Jinsong Li (Journal of Biosafety and Biosecurity, 2019)
Biosafety laboratory risk assessment is a dynamic and systematic work. The scope of the assessment involves evaluation of pathogenic microbial hazards, experimental activities, facilities and equipment, personnel, experimental methods, etc. The four-level evaluation method for pathogenic microorganisms is used for hazard assessment. The aerosol exposure risk is the most common in experimental activities. Facilities and equipment are the basis for the safe operation of biosafety laboratories. Laboratory biosafety risk assessments should be conducted regularly to ensure the safe operation of the laboratory. Keywords: Biosafety laboratory, Risk assessment, Pathogenic microbial